Modelling Financial-Accounting Decisions by Means of OLAP Tools - Diana Elena CODREAN (Database Systems Journal, 2011)
At present, one can say that a company’s good running largely depends on the information quantity and quality it relies on when making decisions. The information needed to underlie decisions and be obtained due to the existence of a high-performing information system which makes it possible for the data to be shown quickly, synthetically and truly, also providing the opportunity for complex analyses and predictions. In such circumstances, computerized accounting systems, too, have grown their complexity by means of data analyzing information solutions such as OLAP and Data Mining which help perform a multidimensional analysis of financial-accounting data, potential frauds can be detected and data hidden information can be revealed, trends for certain indicators can be set up, therefore ensuring useful information to a company’s decision making.